If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 39 = 0 Reorder the terms: 39 + 3x = 0 Solving 39 + 3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-39' to each side of the equation. 39 + -39 + 3x = 0 + -39 Combine like terms: 39 + -39 = 0 0 + 3x = 0 + -39 3x = 0 + -39 Combine like terms: 0 + -39 = -39 3x = -39 Divide each side by '3'. x = -13 Simplifying x = -13
| 3i*3i= | | -0.9(7.5w-6)-9= | | i*3i= | | 9(x-4)+x=10(x-4)+4 | | .02=15.4 | | -5x+3.6=2.1-4x | | 7.5(-0.9w-9)-6= | | x^2+2=3y | | 3x^3+5x-24=0 | | 4x+8x=2(6x-12) | | 4(8-5x)=25 | | -8+22=15x-2-14x | | (8a-5x)2= | | x-6=-2-24 | | -47.62=k+89.2 | | 2x^2+22x+54=0 | | (7+3y)2= | | 6x=3(2x+5) | | 180k^2+300k+125=0 | | 6m-(31m-18)=12(m-1)+3m | | y=8-(1/2)x | | 160x^2-250=0 | | -3c^2+4c-4= | | h=25433(9.5)+28.465 | | 6x+8-4x=20 | | 4(k-2)-6=3k-(2k-3) | | m+m+18=31 | | 243g^2+54g+3=0 | | 61*ln(y)=13 | | 4/3p=9/8 | | 5(2x-6)=25 | | 2(p+9)= |